Evaluation of intra-abdominal adhesion formation after laparoscopic ventral hernia repair with composite mesh using abdominal ultrasound: a prospective observational study - Arora, Jainendra K.; Sankal, Manjunatha; Ghasi, Rohini Gupta; Thakur, Radhika (International Surgery Journal, 2021)
Background: Laparoscopic ventral hernia repair has revolutionized treatment of ventral hernia by offering shorter recovery time, decreased pain, reduced wound complications and lower recurrence rates as compared to conventional open hernia repair. But intra-abdominal mesh placement is associated with a high risk of complications including adhesions, bowel obstruction and fistula formation. Many different types of meshes with adhesion barriers have been developed to overcome these problems. This prospective observational study evaluated the outcomes of laparoscopic repair of ventral hernias in terms of Intra-abdominal adhesion formation with composite mesh using ultrasound. Methods: The study was conducted from August 2017 to February 2019. All patients underwent standard laparoscopic ventral hernias repair using composite mesh secured with tackers. Omentum was interposed between the mesh and underlying bowel. At a mean follow-up of one year, all patients were subjected to ultrasound examination using visceral slide technique to detect Intra-abdominal adhesions. Results: Our study included 50 patients with a mean age of 43 years (range 26-59 years) and mean body mass index of 29.07±2.35 kg/m2 (range, 24-33 kg/m2). Mean fascial defect size of hernia was 13.4±3.77 cm2 (range12-16 cm2). There were no mesh-related complications and recurrence during the follow-up period of 1 year. Conclusions: Laparoscopic ventral hernia repair using composite mesh seems to be a promising technique for treating ventral hernias. However, longer follow-up periods are needed to confirm effectiveness and safety of the composite mesh.